Development of a didactic system for remote physical training of police employees - Muslimov R.A. (Theory and Practice of Physical Culture, 2023)
The developed electronic textbook allows you to organize the educational process of distance physical training for employees of internal affairs bodies studying by correspondence. The electronic format for structuring system elements allows you to flexibly respond to changes in the general system of professional education of employees and generate various pedagogical technologies. The developed didactic system is nonlinear, open and capable of self-development.